Farmers 'Response To The Nature Of Innovation Pakuwon Biofertilizer Technology To Stimulate Simultaneous Flowering of Coffee Plants - Afrizon Afrizon; Ruswendi Ruswendi; Yulie Oktavia; Andi Ishak; Emlan Fauzi; Shannora Yuliasari (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
Pakuwon biofertilizer is a biological fertilizer that has advantages in synchronizing coffee flowering. This technological innovation was produced by the Research Institute for Industrial Crops and Refreshments (Balitri) of the Agricultural Research and Development Agency which is able to increase the productivity of coffee plants and the efficiency of harvest labor. This study aims to determine the response of farmers to the Pakuwon biofertilizer technology innovation. The research was conducted from June to August 2019 at the Pematang Manggis Farmer Group, Talang Ulu Village, Curup Timur District, which is one of the coffee production centers in Rejang Lebong. Data collection was carried out through survey techniques and demonstrations involving 12 farmers. The data collected is the response of farmers to the nature of Pakuwon biofertilizer technology innovation which includes relative advantage, compatibility, complexity, observability, and triability. The survey to determine the response of farmers was carried out twice, namely the first survey after the socialization of technology and the second survey after the implementation of demonstration methods in the field of 200 coffee plants over 10 years old. Data were analyzed descriptively and statistically using response mapping and the Wilcoxon rank test. The results showed that the attributes of Pakuwon biofertilizer innovation, namely relative advantage, complexity, and triability, increased after the demonstration was carried out, the compatibility attributes were fixed, while the observability decreased. The decreasing observability is assumed because farmers are not sure about the results obtained because they have not seen the results of applying the Pakuwon biofertilizer in the field. Only the complexity attribute increased significantly after the demonstration of how to do it, showing that the application of Pakuwon biofertilizer technology innovation is easy to do in the field.